RANCANG BANGUN SISTEM INFORMASI PENGELOLAAN DAN PELAPORAN KAS RT/RW BERBASIS WEB PADA RT 001/RW 06 KELURAHAN SUDIMARA BARAT MENGGUNAKAN METODE WATERFALL - Dwi Nurcahyo; Farizi Ilham; Abdul Aziez Awal Saputra; Rayhan Maullana Brewiratama (Journal of Research and Publication Innovation, 2026)
RT 001 RW 06 Sudimara Barat has a population of approximately 400-450 families (KK). Currently, the management of contributions and social funds still uses a ledger and is recorded manually, which poses a risk of recording errors, irregular arrears data, and a lack of transparency in financial reports. The objective of this KP is to design a web-based cash management application to improve data accuracy and transparency. The development method uses the SDLC waterfall (analysis, design, program implementation, testing) approach. Data collection was conducted through interviews with the RT head, observations, and literature review. The project scope includes several key features, including a real-time dashboard, resident data management, contribution recording, social fund management, payment validation, monthly or annual report data correction, contribution notifications, and PDF report printing. The expected outcomes are minimizing manual recording errors, assisting RT administrators in monitoring residents' social funds, and providing transparent financial reports for all residents.